Superconductivity in magnetically ordered Ru1-xIr xSr2GdCu2O8 compounds - Andrade,S. (2003)
We have performed a systematic study of the structural, transport, and magnetic properties of polycrystalline samples of the magnetic superconductors Ru1-xIr xSr2GdCu2O8; x = 0, 0.02, 0.05, 0.10, and 0.15. The samples were prepared by solid state reaction and sintered at 1060 ºC for 72 h under O2 flow. X-ray diffraction analysis shows that all samples are nearly single phase and that the lattice parameters are independent of Ir content. Transport properties measurements revealed that the Ru substitution by Ir results in a decrease of Tc,onset from ~50 K (x = 0) to ~30 K (x = 0.10). Further addition of Ir (x > 0.10) causes an evolution from metallic to nonmetallic behavior of r(T). We have also found that magnetic order develops in the undoped Ru-1212 materials near T M ~ 130 K. This temperature decreases linearly with increasing Ir content at the rate of ~ -1.6 K / Ir at.%, suggesting that Ir effectively substitutes Ru in the RuO planes. A subtle drop in r(T) is observed close to T M, probably due to the suppression of the spin-flip scattering. The magnetoresistivity measurements revealed that the temperature Tc,zero, in which r(T) ~ 0, decreases rapidly for low applied magnetic fields (H < 2 T), and that this drop becomes much less pronounced in higher magnetic fields (2 < H < 18 T). The appreciable broadening of r(T) curves at low magnetic fields is reminiscent of the behavior in high-Tc materials showing granular behavior, as for example in Sm1.85Ce0.15CuO4-y.